Dealing with quantitative easing spillovers in East Asia: The role of institutions and macroprudential policy - Ayako Saiki; Pornpinun Chantapacdepong; Ulrich Volz (Asian Development Bank Institute (ADBI), 2016)
This paper explores the impact of advanced countries' quantitative easing on emerging market economies (EMEs) and how macroprudential policy and good governance play a role in preventing potential financial vulnerabilities. We used confidential locational bank statistics data from the Bank for International Settlements to examine whether quantitative easing has caused an appreciation of EMEs' currencies and how it has done so, and whether this has in turn boosted foreign-currency borrowing, thus making EMEs vulnerable to balance sheet and maturity mismatch problems. While focusing our analysis on East Asian economies, we compare them with Latin American economies, which were also major recipients of quantitative easing capital inflows. We found that government effectiveness plays an important role in curbing excessive borrowing when the exchange rate is overvalued.
Keywords: E44; E58; F31; F32; F34; 330; Quantitative easing; spillover effects; macroprudential policy; good governance; capital inflows; emerging market economies (EMEs); East Asia; Latin America